PENGGUNAAN MEDIA SOSIAL BERBASIS PEMBELAJARAN BAHASA ASING HELLOTALK BAGI PENUTUR ASING (Kajian sintaksis) - Puji Lestari (JURNAL KONFIKS, 2018)
HelloTalk be an alternative solution that is effective and efficient in learning SPEAKER because SPEAKER participants can apply the theory acquired in class. This study sheds light on when the SPEAKER in the learners chat rooms or through status-status of the written chat friends, revised the grammatical errors that tend to be confusing for the participants of the SPEAKER. This research aims to describe and explain the form of syntactic errors accompanied the form pembenarannya conducted by six informants, namely the account Charlesinoz (United States), HEEJAEPark (South Korea), Vince (Australia), Shachi. Chi (China), Sabri Sab (Pakistan), and Joseph (United Kingdom). This research uses qualitative descriptive approach. Data collection techniques used are tuned and note techniques. Data analysis was done by utilizing techniques in accordance in accordance with the method of referential, pragmatic, and match and read landmark. Results of the study concluded the form error fields syntax, i.e.: (1) raw and not structured sentences not bergramatikal, (2) the ambiguous sentence (3) sentences that are unclear, (4) the inappropriate diction in sentence form, (5) contamination of the sentence, (6) coherence, (7) the use of the word redundant, (8) loan words that are not exactly in the form of a sentence, and (9) the logic of the sentence. The research also shows most do mistakes, i.e. the use of the word is not raw or sentence is not grammatical. HEEJAEPark dominated with a total of 25 forms of error field syntax.